The Cambridge atlas of Herschel objects - Mullaney, James, 1940- (Cambridge University Press, 2011)
"This superb, all-purpose star atlas is the first of its kind devoted to observing the Herschel objects with binoculars and telescopes. It displays over 2500 of the most visually-attractive star clusters, nebulae and galaxies that were discovered by Sir William, Carolyn and Sir John Herschel, and is a must-have for stargazers who want to explore these fascinating objects. Covering the entire sky from the North to the South Celestial Pole, and showing all 88 constellations, it is also a general sky atlas showing variable, double and multiple stars, and the Milky Way. Written by experienced observer James Mullaney and illustrated by renowned celestial cartographer Wil Tirion, this is a magnificent 'celestial roadmap' to some of the finest deep-sky showpieces. Spiral bound and printed in red-light friendly colors for use at a telescope, with color-coded symbols for easy recognition and identification, this is an all-purpose observing reference for all amateur observers"--